Application of KBaYSi2O7:Bi3+,Eu3+ Phosphor for White Light-Emitting Diodes with Excellent Color Quality - Loan, Nguyen Thi Phuong; Thuy, Le Xuan; Thai, Nguyen Le; Lee, Hsiao Yi; Cong, Pham Hong (Science and Technology Indonesia, 2024)
This paper examines the properties of two phosphor materials synthesized via utilizing the sol gel method: KBaYSi2O7:Bi3+ (KBYS:Bi) phosphor providing cyan/deep-blue emission and KBaYSi2O7:Bi3+,Eu3+ (KBYS:Bi,Eu) phosphor exhibiting tunable emission from near-UV to red. The optimal doping concentrations for Bi3+ and Eu3+ are 0.2% and 3.5%, respectively. It is found that the ability to give discrepant emission peaks under different excitation sources of the KBYS:Bi phosphor is attributed to the occupancy of Bi3+ in different cation hosts. Meanwhile, co doping the Eu3+ and Bi3+ into the KBYS host leads to red and cyan emission regions, enabling the emission tunability of the KBYS:Bi,Eu phosphor. KBYS:Bi,Eu phosphor was then used in combination with YAG:Ce3+ and blue chips to fabricate a white light emitting diode (LED) model. The particle sizes of KBYS:Bi,Eu phosphor are adjusted to examine its influences on the LED properties. With increasing particle sizes (≥12 µm), the KBYS:Bi,Eu phosphor can improve the scatter efficacy, transmission power, lumen output, and color performance (rendition and uniformity). Both KBYS:Bi and KBYS:Bi,Eu phosphors are promising luminescent phosphors that can be combined with other phosphor with different emission colors to obtain the full-spectrum or tunable white light for LEDs.